DECODING AND SYNOPTIC INTERPRETATION OF INFRARED (IR) CLOUD COVER PHOTOGRAPHS - Dombkovskaya,E. P. (1969)
The article gives a brief description of infrared photographs taken by the Nimbus I meteorological satellite and examples of their interpretation; the materials for the article were taken from the American publication Nimbus I High Resolution Radiation Data Catalog and User's Manual, USA, January, 1965. The article begins with a brief discussion of the principles for interpreting such infrared photographs and then proceeds to a discussion of specific cases. Three of the photographs discussed are for the area of the USSR and one photograph is for the Greenland area. The interpretation is based on the use of aerosynoptic data and a comparison with maps. There is a discussion of the criteria used in interpreting such features as cyclones, warm fronts, cold fronts, and sea surface. The author then formulates four categories of cloud formations which are discussed in considerable detail: (1) cloud bands, (2) cloud vortices, (3) dense cloud shields, and (4) cloud formations with clearings. (Author) Trans. from Gidrometeorologicheskii Nauchno-Issledovatelskii Tsentr SSSR. Trudy, n11 1967.